Metalloenzymes as Inspirational Electrocatalysts for Artificial Photosynthesis From Mechanism to Model Devices - Bachmeier, Andreas S. J. L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This thesis describes a series of investigations designed to assess the value of metalloenzymes in systems for artificial and adapted photosynthesis. The research presented explores the interplay between inherent enzyme properties such as structure, rates and thermodynamics, and the properties of the semiconducting materials to which the enzyme is attached. Author, Andreas Bachmeier provides a comprehensive introduction to the interdisciplinary field of artificial photosynthesis, allowing the reader to grasp the latest approaches being investigated, from molecular systems to heterogeneous surface catalysis. Bachmeier's work also uses metalloenzymes to highlight the importance of reversible catalysts in removing the burden of poor electrocatalytic rates and efficiencies which are common characteristics for most artificial photosynthesis systems. Overall, this thesis provides newcomers and students in the field with evidence that metalloenzymes can be used to establish new directionsin artificial photosynthesis research.
Introduction -- Theory of experimental techniques -- The mechanism of [FeFe]-hydrogenases - How Aldehydes Inhibit H2 Evolution -- The Direct Electrochemistry of Fuel-Forming Enzymes on Semiconducting Electrodes: How Light-Harvesting Semiconductors can Alter The Bias of Reversible Electrocatalysts in Favour of H2 Production and CO2 Reduction -- Selective Visible-Light-Driven CO2 Reduction on a p-type Dye-Sensitised NiO Photocathode -- A Multi-Haem Flavoenzyme as a Solar Conversion Catalyst -- Conclusions and Perspectives -- Experimental Section -- Bibliography.
Keywords: Physical chemistry; Catalysis; Renewable energy sources; Enzymology; Physical Chemistry; Catalysis; Renewable Energy; Enzymology